Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1210/clinem/dgab167
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Butyl Paraben Is Associated With Fat Percentage in 7-Year-Old Boys

Abstract: Context Parabens are used as preservatives in consumer products but are suspected of having endocrine-disrupting properties. A recent study reported an association between in utero exposure to butyl paraben and overweight in childhood, with a stronger trend in girls. Objective We therefore studied the association between parabens in maternal urine in third trimester and fat percentage in children aged 7 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ]. Early life exposure to parabens is associated with increases in the gestational weight gain (GWG) rate [ 32 ], changes in height, head, hip, or arm circumference [ 28 , 30 , 33 , 34 ], z-scores of bodyweight [ 35 ], BMI or BMI z-scores [ 31 , 36 , 37 ], and overweight status in early childhood [ 38 ], although the direction of associations depends on the type of parabens and gender ( Table 1 ). However, results from one large-scale (n = 1015 mother–child pairs) and one small-scale study (n = 99 mother–newborn pairs) did not show any clear association.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of these studies showed that parabens could cross the placental barrier [ 28 , 29 , 30 , 31 ]. Early life exposure to parabens is associated with increases in the gestational weight gain (GWG) rate [ 32 ], changes in height, head, hip, or arm circumference [ 28 , 30 , 33 , 34 ], z-scores of bodyweight [ 35 ], BMI or BMI z-scores [ 31 , 36 , 37 ], and overweight status in early childhood [ 38 ], although the direction of associations depends on the type of parabens and gender ( Table 1 ). However, results from one large-scale (n = 1015 mother–child pairs) and one small-scale study (n = 99 mother–newborn pairs) did not show any clear association.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogens play a critical role in the development of obesity [ 46 , 47 ] and parabens interfere with the estrogen metabolism pathway [ 48 , 49 ]. In vitro maternal butylparaben (BuP) exposure increases the weight of female offspring, but not male offspring mice [ 37 ], which may support the observed gender-specific effects in some of the studies, although the latter has not been consistent ( Table 1 ) [ 30 , 33 , 34 , 35 , 36 , 37 , 41 ]. Both estrogen and androgen are critical in regulating adiposity and metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations